The impact of the social isolation in elderly Brazilian mental health (anxiety and depression) during the COVID-19 pandemic - Sousa, Isabella Louise Morais de; Silveira, Rodrigo; Takito, Mônica Yuri; Pereira, Adenilson Leão; Lucianelli-Júnior, Dalberto; Carmona, Giselle Sousa; Viegas, Ana Paula do Vale; Teixeira, Francisco Bruno; Santos, Ozélia Sousa; Valentin, Fernanda Nogueira (Frontiers in Psychiatry, 2022)
The impact of the social isolation in the pandemic context on the elderly brazilian mental health is little known, especially about the occurrence of depressive symptoms. In this study, we evaluated elderly people undergoing social isolation in order to identify factors associated to depression and which of these are more important to characterize depressive brazilians elderly. In a cross-sectional, exploratory and analytical study of a quantitative nature, the mental profile of elderly individuals subjected to social isolation during the COVID-19 pandemic period was used. The 450 participants were divided in normal and depressive groups, and a form covering sociodemographic data, opinions/perceptions about the pandemic and a Reduced Geriatric Depression Scale was used to assess participants' mental health. To assess the statistical significance between the variables, chi-square test was applied, considering p-value <0.05. The effect size was analyzed to identify the magnitude of difference between groups. To identify the most important characteristics to define the groups Multilayer Perceptron algorithm were applied. We found that elderly people with a depressive profile are (in Multilayer Perceptron rank order): (1) Shows signs of anxiety during the COVID-19 pandemic, (2) Low education, (3) Being divorced, (4) Having more than one mental disorder, (5) Reading, watching or listening to information about COVID-19, (6) Being previously diagnosed with depression. In conclusion, elderly Brazilians in social isolation tend to develop depressive disorders during quarantine. Thus, we can consider that the pandemic requires effective and safe gerontological care and monitoring, especially with regard to mental health.